Coal measure energy production and the reservoir space utilization in China under carbon neutral target - Chen, Run; Bao, Yunxia; Lv, Fengrong; Chen, Fu; Hu, Kunpeng; Zhang, Yajun (Frontiers in Earth Science, 2023)
Coal measure energy production and reservoir space utilization are both important for energy security and can assist in achieving carbon neutrality. Coal measure energy production and reservoir utilization are therefore of scientific significance. This study focuses on the security of coal supply by discussing the possible technical approaches of combining low-carbon mining of coal measure resources and coal reservoir space utilization. Our study found that 1) the integration of underground coal gasification and carbon capture and sequestration (UCG-CCS) is an effective technology to improve energy efficiency and achieve the carbon neutral target in China; 2) CO2-enhanced coalbed methane (CO2-ECBM) recovery is an important way to reduce CO2 emissions during coalbed methane recovery; and 3) the integrated technology of solid waste filling (WF), coal bioconversion (CB), gas production (GP), and CO2 capture and sequestration (CCS) in coal goafs and abandoned coal mines can improve the energy production efficiency and reservoir space utilization and reduce geological disasters due to surface subsidence. These integrated technologies will become increasingly important for coal measure energy production and efficient reservoir space utilization as they will provide scientific theory and technical support to achieve carbon neutrality.